2015
DOI: 10.1093/humrep/dev113
|View full text |Cite
|
Sign up to set email alerts
|

Fucosylated clusterin in semen promotes the uptake of stress-damaged proteins by dendritic cells via DC-SIGN

Abstract: The present research was supported by the Consejo Nacional de Investigaciones Científicas y Técnicas, the Buenos Aires University School of Medicine, and the Agencia Nacional de Promoción Científica y Tecnológica (Argentina). The authors have no conflicts of interest to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…The fact that serum CLU does not demonstrate such features is interesting. Merlotti et al (2015) proved that seminal plasma CLU plays an important role in the utilization of damaged proteins. CLU inhibits aggregation of the destroyed proteins and forwards them to the DCs through DC‐SIGN.…”
Section: The Role Of Clu Glycosylationmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that serum CLU does not demonstrate such features is interesting. Merlotti et al (2015) proved that seminal plasma CLU plays an important role in the utilization of damaged proteins. CLU inhibits aggregation of the destroyed proteins and forwards them to the DCs through DC‐SIGN.…”
Section: The Role Of Clu Glycosylationmentioning
confidence: 99%
“…The interactions between DCs and CLU result in DCs stimulation. Merlotti et al (2015) presumed that it might be essential in the induction of immune tolerance in the female reproductive tract.…”
Section: The Role Of Clu Glycosylationmentioning
confidence: 99%
“…29 Semen mediates the expansion of Tregs in DLN of the genital tract and their subsequent recruitment to the uterine endometrium. 1,13 This tolerogenic response is induced even in the absence of conception, suggesting a major role for SP in eliciting this effect. 11 Moreover, it was shown to be completely dependent on the presence of SVF, as mating with seminal vesicle-deficient males failed to induce the expansion of Tregs.…”
Section: Discussionmentioning
confidence: 92%
“…12 Moreover, we also showed that a protein found at high concentrations in the SP, clusterin, promotes the expansion of Tregs by DCs. 13 A very important question that remains to be answered is whether deposition of SP in the female reproductive tract might also be capable of suppressing the adaptive immune response against pathogens in a similar way to the immune response against paternal antigens. As semen is the main vector for sexually transmitted infectious diseases that annually causes millions of deaths in the world, 14 it is striking that the ability of semen to modulate the course of the anti-microbial immune response has not been analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…CLU present in the rete testis fluid is synthesized by Sertoli cells and adheres to the surface of testicular spermatozoa. When spermatozoa move through the rete testis and efferent duct, testis-derived CLU is replaced by CLU from the epididymal or seminal vesicle (Griffiths et al, 2009).CLU expression is negatively associated with the percentage of normal sperm morphology (Santos et al, 2014) and high expression of CLU promotes the uptake of stress-damaged proteins by dendritic cells in male reproductive tract (Merlotti et al, 2015).…”
mentioning
confidence: 99%